Islamic bioethics current issues and challenges - Bagheri, Alireza; Alali, Khalid (Intercultural dialogue in bioethics, 2018)
Islamic Bioethics presents a wide variety of perspectives and debates on how Islamic societies deal with the ethical dilemmas raised by biomedicine and new technologies. The book is a "constructive dialogue" between contributors selected from a multidisciplinary group of Muslim and non-Muslim scholars from different Islamic countries. The 11 chapters illuminate the diversity and complexity of the issues discussed in Islamic bioethics and pave the way to a better understanding of Islamic bioethics and dialogue in the global bioethics community. The chapters take both theoretical and practical approaches to the topic, and each covers an emerging issue in Islamic bioethics. This book will be useful for academics and professional institutions in both Islamic and non-Islamic countries, and will be instrumental in providing researchers, scholars, students, policymakers and medical professionals with access to the latest issues and debates related to Islamic bioethics.